2019
DOI: 10.3390/c5030048
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Stability and Local Piezoelectrical Properties of P(VDF-TrFE)/Graphene Oxide Composite Fibers

Abstract: The unprecedented attributes such as biocompatibility and flexibility of macromolecular piezoelectric polymer has triggered an immense interested in scientific society for their potential exploitation in implantable electronic devices. In the present article, a theoretical and experimental investigation is done to explore the polarization behavior of composite fibers based on copolymer poly-trifluoroethylene P(VDF-TrFE) and graphene oxide (GO) with varying composition of the components is explored for its poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Xu et al [296] studied PVDF/(γ-oxo-pyrenebutyric acid)-modified graphene and BaTiO3 reporting the improvement of dielectric constant and this effect was not only caused by high dielectric constant of BaTiO3 but also by polarization of the nanofillers. Zhou et al [118] reported BaTiO3@carbon nanoparticle-enabled P(VDF-TrFE) composites for the application in PENGs (GO -P(VDF-TrFE) composite fibers were also studied [297]). Also, rGO-PVDF-TrFE materials emerged as very interesting wearable energy generators (WNGs) [93] -Fig.…”
Section: Practical Applications Of Pvdf-cnms In Various Generatorsmentioning
confidence: 99%
“…Xu et al [296] studied PVDF/(γ-oxo-pyrenebutyric acid)-modified graphene and BaTiO3 reporting the improvement of dielectric constant and this effect was not only caused by high dielectric constant of BaTiO3 but also by polarization of the nanofillers. Zhou et al [118] reported BaTiO3@carbon nanoparticle-enabled P(VDF-TrFE) composites for the application in PENGs (GO -P(VDF-TrFE) composite fibers were also studied [297]). Also, rGO-PVDF-TrFE materials emerged as very interesting wearable energy generators (WNGs) [93] -Fig.…”
Section: Practical Applications Of Pvdf-cnms In Various Generatorsmentioning
confidence: 99%
“…To our knowledge, graphene is not commonly used in molten polymers as a processing aid agent or lubricant, but it could be an interesting candidate given its tribological properties [15]. In addition, it would complement the unique combination of functionalities of graphene, such as high mechanical strength, electrical conductivity [16][17][18], UV resistance [19], piezoelectric response enhancement [20], as well as the valorization of recycled plastics and mixed plastic waste streams [21,22]. Furthermore, recent toxicity studies performed on few-layer graphene industrial grades produced by the mechanochemical exfoliation of graphite have much lower health and safety concerns than other nanocarbons such carbon nanotube and carbon black [23].…”
Section: Introductionmentioning
confidence: 99%